A tribute to Dr. Samuel McDonald McCann’s life as a scientist, mentor and friend - Mastronardi, Claudio A. (2009)
We have had the honor and pleasure to have worked and shared a sincere and unique friendship with Dr. S.M. McCann. Dr. McCann was a unique person: enthusiastic, inspiring and a terrific scientist whose passion for science and knowledge were limitless. His scientific achievements as a pioneer of the two interrelated fields of neuroendocrinology and neuroimmunomodulation included more than 1,000 publications and a number of outstanding scientific prizes. Above all, Don was a generous, talented mentor and fostered the career of several young scientists, who have become world-renowned academic leaders in leading universities and research centers. This mini-review focuses on our collaborative work with Dr. McCann, providing evidence for a bidirectional communication between the neuroendocrine and -immune systems. Interestingly, it is believed that chronic stress can alter the balance between this bidirectional interaction and eventually cause psychiatric disorders (20).